Resource discovery in ASON GMPLS transport networks. - Perello, Jordi (IEEE Communications magazine)
Automatic resource discovery plays a significant role in next-generation optical networks, where nodes can maintain a large number of input/output ports (fibers, wavelengths, time slots, etc.). This automation avoids long and tedious manual node configurations and minimizes resource misconfiguration probability, which can result in high cost savings for network operators. The generalized multiprotocol label switching (GMPLS) Link Management Protocol (LMP) has been defined to provide such functionalities. However, it requires optical nodes to transmit in-band information, thus requesting link termination on each incoming port. This issue, in transparent optical networks, implies additional hardware, high complexities, or even signal losses. This article proposes and evaluates novel extensions to standard LMP that cope with the discovery of all-optical transport planes. In addition, playing a crucial role in ASON/GMPLS networks, this article also generically covers the automatic discovery of the control plane.